ORGANIZATIONAL LEARNING CULTURE AS MODERATOR ON THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND AFFECTIVE COMMITMENT - Luthfia Putri Rizki (Hasanuddin Economics and Business Review, 2021)
The aim of this study is to investigate the effect of organizational learning culture as moderator on the relationship between transformational leadership and affective commitment. Framework in this study use Social Exchange Theory to explain the moderation effect and we argue that the relationship between transformational leadership and affective commitment is strengthened by organizational learning culture. Data were collected by administering questionnaires to the respondents using both offline and online survey on employees from startup companies in Indonesia (N = 73). This study using self-report method and data were analyzed using Hayes’ PROCESS macro on SPSS software. Results showed that organizational learning culture moderated the relationship between transformational leadership and affective commitment, such that the relationship was increased when organizational learning culture was high than when organizational learning culture was low. Moreover, theoretical and practical implications are given to improvement of employees’ affective commitment.